Minimizing acetate formation from overflow metabolism in Escherichia coli: comparison of genetic engineering strategies to improve robustness toward sugar gradients in large-scale fermentation processes - Gecse, Greta; Labunskaite, Rugile; Pedersen, Margit; Kilstrup, Mogens; Johanson, Ted (Frontiers in Bioengineering and Biotechnology, 2024)
reducing the glucose uptake rate showed no effect in this study despite being previously shown as a very effective strategy to reduce acetate formation from overflow metabolism.-Human milk oligosaccharide 2'FL -2'-O-fucosyllactose TCA cycle -Tricarboxylic acid cycle PTS -Phosphotransferase System µmax -Maximum specific growth rate (h -1 )Yas -Acetate yield (g acetate/g glucose) Yps -Product yield (g 2'FL/g glucose) Ypx -Specific product yield (g 2'FL/g biomass) Yxs -Biomass yield (g dry biomass/g glucose) qs -Specific substrate consumption rate (g glucose/OD/h) DO -Dissolved oxygen content in the broth (% of saturation in the medium at atmospheric pressure and 33°C) OD -Optical density measured at 600 nm in 1cm light path.